Effect of Ultrasonic Treatment on the Properties of PSE-like Chicken Sarcoplasmic Protein and Myofibrillar Protein Composite Gels - LI Ke, SUN Lixue, ZHOU Yanfang, ZHANG Yixue, HE Xiangli, DU Manting, MA Wuchao, BAI Yanhong (Shipin Kexue)
Myofibrillar protein (MP) and sarcoplasmic protein (SP) were extracted from pale, soft and exudative (PSE)-like chicken. The research investigated the differences in the heat-induced gel properties of SP-MP blends at 1:9, 2:8 and 3:7 ratios (m/m) and pure MP in order to select the appropriate SP/MP ratio. Furthermore, the differences in the gel properties, water distribution, intermolecular forces, gel electrophoresis pattern and microstructure of composite gels of SP treated with different ultrasonic powers (0, 300 and 600 W) at 20 kHz and MP were studied. The results showed that compared with the pure MP gel, the gel strength and water retention of the composite gel increased first and then decreased with the increase in SP addition, reaching the highest level at an SP/MP ratio of 2:8. After ultrasonic treatment at 600 W, the gel strength and water retention of the 2:8 composite gel were elevated by 113% and 47%, respectively, compared with those of the control group. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) analysis showed that SP had a certain promotion effect on the aggregation and cross-linking of myosin, but this effect became weaker when the ratio of SP to MP was 3:7. Both hydrophobic interactions and disulfide bond content reached their highest levels and the composite gel formed a denser network structure when the ratio of SP to MP was 2:8, and the ultrasonic power was 600 W. In conclusion, the effect of addition of ultrasonic-treated SP on the gel-forming capacity of PSE-like chicken MP was related to its concentration, and ultrasonic-treated SP favored the formation of MP gel structure, which effectively improved the gel characteristics of PSE-like chicken MP.